Smart Agriculture Solutions for Vietnamese Farmers - Vu, Chien-Thang (EAI Endorsed Transactions on Internet of Things, 2022)
Agriculture is the back bone of Vietnam and more than 70% of people in Vietnam depend on agriculture. Nowadays, agriculture crops are affected due to many environmental changes. To overcome this problem, I design and prototype a wireless sensor and actuator network for smart agriculture application. The aim of this work is to be able to capture useful data to start predicting measurements and events that could help farmers and specialists to save time and money. I propose two solutions for smart agriculture. In the first solution, wireless sensor and actuator nodes monitor multiple environmental parameters and transmit the sensor data to a server via the internet. Users can monitor these environmental parameters from anywhere via the internet. In the second solution, wireless sensor and actuator nodes send data to a local computer. This computer is deployed in a technical room. The experiments show that both solutions operate well in real conditions.
Keywords: smart agriculture; internet of things in agriculture; wireless sensor and actuator networks; greenhouse